In-situ characterization of thin polyimide films used for microelectronic packaging - Windrich, Frank; Malanin, Mikhail; Bittrich, Eva; Schwarz, Alexander; Eichhorn, Klaus Jochen; Voit, Brigitte (2018 7th Electronic System-Integration Technology Conference, ESTC 2018 - Proceedings, 2018)
Different in-situ methods were utilized to study thin film polyimide layers in the context of low-temperature cure processes <230°. In-situ Fourier Transform Infrared Spectroscopy, temperature dependent Spectroscopic Ellipsometry and Thermal Analytical Methods were used to characterize the degree of imidization, glass transition temperature and thermal stability respectively. The final degree of imidization in the low-temperature cure region depends strongly on the UV induced network formation during the upstream Iithographic process. A higher crosslinking density reduces the degree of imidization from 97.5% for an unexposed layer to 73.2% for higher crosslinked film. Glass transition temperature and thermal stability are significantly reduced in the case of curing temperatures below 230°C. The glass transition temperature is decreased from 240°C to 218°C for cure temperatures of 350°C and 230°C respectively. The yielded film stress is reduced in parallel, which was proved by determination of wafer warpage and bow.
CRIS-Team Scopus Importer:2022-04-14
Keywords: low temperature cure; polyimide; redistribution layer; thin film polymer